Interest in Purchasing In-Game Content Based on Game Characteristics and Indonesian Player Behaviour - Agung Riyadi; Riwinoto Riwinoto (CESS (Journal of Computer Engineering, System and Science), 2021)
This research aimed to find out what games are currently being played and how many contents purchased in them. Information regarding the interest in purchasing the game contents is crucial for the game developers to determine the game type to be developed. The research used a survey method conducted on 455 respondents aged 18-30 years from Indonesia. The survey results stated that most Indonesian game players were in the Regular Player category who played Action games with a population of 71%. The amount of interest in purchasing the contents from the Frequent Players towards Action and RPG games was 92%. As for games in the Puzzle category, the amount of interest in purchasing the contents was very small. 96% of puzzle game players certainly had no interest in purchasing the contents.